Viral infection proï¬le in Pediatric Dermatology Division clinic of Dermatology and Venereology Outpatient Dr. Soetomo General Hospital Surabaya - Prabawaningrum, Kinanti; Zulkarnain, Iskandar (Faculty Of Medicine Airlangga University, 2015)
Background: Viral infections are common in children and distributed widely in the world. There are not many studies that discuss the proï¬le of viral infection in children in East Java. Purpose: To evaluate viral infections patients proï¬les in the Pediatric Dermatology Division Dermatovenereology Outpatient Clinic of Dr. Soetomo General Hospital in 2008-2010 including prevalence, demographic data, type of infection, patient complaints, skin lesions and management. Methods: A retrospective study using medical records for the period January 2008-December 2010. Basic data (age , gender), history (chief complaint, began to arise, disease history), examination (morphology) and treatment (therapy, repeat visits) were recorded. Results: Viral infection patients as much as 285 patients (6.5 % of all pediatric patients at URJ). Most found diagnosis is molluscum contagiosum (40.4%), in the age group 5-14 years (68.4 %), highest complaints pimples (42.8 %) , most duration of diseases >10 days (40 %). Most management actions in the cosmetics division (61.1 %). Conclusion: Viral infection patients in Pediatric Dermatology Division clinic of Dermatology and Venereology Outpatient Dr. Soetomo General Hospital Surabaya in 2008-2010 is likely to increase each year and require a more comprehensive management.Key words : viral infection, child, RSUD Dr. Soetomo.